Role of Dentists in the Management of Behcet’s Disease: A Case Report - Patoni, Nurfianti Ahmad; Sitheeque, Mohaideen AM.; Sarsito, Afi Savitri; Soegyanto, Anandina Irmagita; Wimardhani, Yuniardini Septorini (UI Scholars Hub, 2018)
Behcet’s disease (BD) is a multi-system recurrent inflammatory disorder occurring in the form of vasculitis of an unknown etiology. It most frequently affects oral and genital mucosa, skin, eyes, joints, and blood vessels. The definitive diagnosis of BD is based on major symptoms such as recurrent oral and genital ulcers and recurrent skin and ocular lesions, accompanied by symptoms related to various systems. However, early BD manifestations are very similar to recurrent aphthous stomatitis (RAS). Several years from its first appearance are often required for a definitive diagnosis. Objective: To describe a dentist’s role in BD management in a patient with a history of highly recurrent RAS. Case Report: We evaluated a 38-year-old man with a 10-year history of recurrent oral ulcers, accompanied by skin and eyes lesions. His intraoral examination revealed multi-sized ulcers with a yellowish-white base and regular edges, surrounded by an erythematous halo. Ulcers were located on the tongue, floor of the mouth, and gingival mucosa. Although BD diagnosis was not histopathologically confirmed, the patient’s lesions met the International Criteria for Behcet’s disease with a score of 5. Oral ulcers were managed with chlorhexidine mouthwash 2 times/day and supportive measures. A multidisciplinary approach was used for this patient to provide comprehensive treatment. Conclusion: Dentists can be the first clinicians to detect the possible development of BD in patients with symptoms similar to RAS, but additionally having skin and eye lesions.